Researches on Anti-reflection Coating (ARC) Methods Used in PV Systems - (:unkn) unknown (My University, 2018)
With the development of PV systems’ technologyover the years and the reduction of production costs, PV systemsare now being used for electricity generation. PV systems are listedamong the renewable energy sources as the only requirement issolar energy and electricity generation is carried out without anyfuel and waste. Solar cells used in PV systems are adverselyaffected by extremes of temperature, shading, reflection, andpollution. It is known that before sunrays reach the cell’s surface,some of them disappears from the protective glass surface and arereflected back from the cell through the glass surface. Antireflectioncoatings (ARC) are used to reduce the energy loss andincrease solar cell efficiency and output power. SiO2 and MgF2 arethe most commonly used solutions among these coatings. It hasbeen seen that the most efficient applications, with anti-reflectioncoatings as single, double, triple and more layers, are in triplelayers applications. It has been observed that applications to theprotective glass surface have self-cleaning properties, and TiO2and ZrO2 are frequently used for this. The reflectance index of theprotective glass, which is normally 1.51, can be reduced to 1.20 insilicone cells and 1.28 in thin film surfaces with the AR coatings.
Keywords: Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Sibernitik; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; Mühendislik, Biyotıp; Mühendislik, Elektrik ve Elektronik; Yeşil, Sürdürülebilir Bilim ve Teknoloji; Telekomünikasyon